Viscosity approximation methods for multivalued nonexpansive mappings in geodesic spaces - Bancha Panyanak (2018)
© 2015, Panyanak and Suantai. We prove strong convergence of the viscosity approximation method for multivalued nonexpansive mappings in CAT(0) spaces. Our results generalize the results of Dhompongsa et al. (2012), Wangkeeree and Preechasilp (2013) and many others. Some related results in R-trees are also given.